Mapping and validation of major and stable QTL for flag leaf size from tetraploid wheat. Issue 4 (5th August 2022) - Wang, Jian; Liu, Hang; Zhao, Conghao; Tang, Huaping; Mu, Yang; Xu, Qiang; Deng, Mei; Jiang, Qiantao; Chen, Guoyue; Qi, Pengfei; Wang, Jirui; Jiang, Yunfeng; et al.
Abstract: The flag leaf is an important photosynthetic organ of wheat ( Triticum aestivum L.). Appropriate flag leaf size can effectively increase grain yield. In this study, a tetraploid wheat population of recombinant inbred lines (RILs) and a genetic map constructed based on a wheat 55K single‐nucleotide polymorphism (SNP) array were used to identify quantitative trait loci (QTL) for flag leaf length (FLL), flag leaf width (FLW), flag leaf area (FLA), and the flag leaf length/width ratio (FLR). A novel and major interval flanked by markers AX‐111633224 and AX‐109317229 was identified. This interval includes QTL for FLL ( QFll.sau‐AM‐4B.2 ), for FLW ( QFlw.sau‐AM‐4B.4 ), for FLA ( QFla.sau‐AM‐4B ), and for FLR ( QFlr.sau‐AM‐4B ). Based on the genotypes of the closely linked KASP (Kompetitive allele‐specific polymerase chain reaction [PCR]) marker ( KASP‐AX‐108756198 ), QFlw.sau‐AM‐4B.4 and QFla.sau‐AM‐4B were successfully verified in two F3 populations with different genetic backgrounds. Genetic associations between flag leaf‐related traits and other agronomic traits were detected and analyzed. Four genes in this interval were likely involved in the growth and development of the flag leaf size. In conclusion, this study provides clues for excavating genes related to flag leaf size and breeding variety with ideal plant structure. Core Ideas: This study identifies quantitative trait loci (QTL) for flag leaf‐related traits in tetraploid wheat. QTL were identified using an RIL population and a wheat 55K SNP array‐based constructed genetic map. The genetic effects of the major and stable QTL for flag leaf‐related traits were validated in other genetic backgrounds. Tightly linked KASP marker ( KASP‐AX‐108756198 ) can be further used in molecular marker‐assisted selection.